Cu/ZnO/Al2O3/Cr2O3/CeO2 Catalyst for Hydrogen Production by Oxidative Methanol Reforming via Washcoat Catalyst Preparation in Microchannel Reactor - Donny Lesmana; Ho Shing Wu (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
The oxidative methanol reforming reaction was carried out using Cu/ZnO/Al2O3/Cr2O3/CeO2 (15/15/2.5/1.25/1.25 mol%), with washcoat by EC sol on microchannel reactor. The experimental conditions were used various sol for washcoat of catalyst, various method for calcinations of catalyst, steam to methanol mole ratio, the mole ratio of oxygen to methanol, weight hourly space velocity, reaction temperature. The experiment result shows that methanol conversion achieved 98.8 % and carbon    monoxide concentration equal to 1204 ppm when using Cu/ZnO/Al2O3/Cr2O3/CeO2 (15/15/2.5/1.25/1.25 mol%) catalyst mixed with EC sol at the reaction temperature of 200 oC.